NILAI KEADILAN DAN NILAI KEMANFAATAN PADA JARIMAH QISAS DAN DIYAT DALAM HUKUM PIDANA ISLAM - Noercholish Rafid (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2022)
This research examines the value of justice and the value of benefit in jarimah qisas and diyat in Islamic criminal law. The type of research is library research using a syar'i normative approach, it is an approach based on the arguments of the Qur'an and hadith. Jarimah qisas diyat applies universally as a form of benefit value for the survival of the community. REFERENCES Abu Zahrah, Muh}ammad . (1998). Al-Jarimah wa al-‘Uqubah fi al-Fiqh al-Islami. Al-Qahirah: Dar al-Fikr al-‘Arabi Al-Maliki, Abdurrahman & Ahmad ad-Da’ur. (2004). Nidzam al-Uqubat dan Ahkam al-Bayyinat/Sistem Sanksi dan Hukum Pembuktian dalam Islam, Penerjemah,Syamsuddin Ramadlan, Bogor: PustakaThariqul Izzah. Arief, Barda Nawawi. (1998). Beberapa Aspek Kebijakan Penegakan dan Pengembangan Hukum Pidana, Bandung: Citra Aditya Bakti. Arrasid, Chainur. (2004). Dasar-dasar Ilmu Hukum, Jakarta: Sinar Grafika. Asse, Ambo. (2010). Konsep Adil Dalam Al-Qur‟an (Jurnal Al-Risalah Volume 10 Nomor 2. Asshiddiqie, Jimly & M. Ali Syafa'at. (2006). Teori Hans Kelsen Tentang Hukum, Jakarta: Konstitusi Press. Atmasasmita, Romli. (1992). Teori Kapita selekta Kriminologi. Bandung: PT Eresco. Darijarkoro. (1985). PidanaMati di Indonesia, Jakarta: Ghalia. Hadana, Erha Saufan dan Beri Rizqi. (2020) Konsep Keadilan Terhadap Delik Pembunuhan (Analisis Komparatif Hukum Islam dan KUHP), Legitimasi, Vol. 9 No 2. Haliman. (1971).  Hukum Pidana Syari’at Islam Menurut Ajaran Ahlus Sunnah. Bulan Bintang, Jakarta. Hamzah, Andi. Sistem Pidana dan Pemidanaan Indonesia Dari Retribusi ke Reformasi. Hanafi. (1990). Asas-AsasHukumPidana Islam, Cet. 4. Jakarta: Bulan Bintang. Helmi, Muhammad. (2015).  "Konsep Keadilan dalam Filsafat Hukum dan Filsafat Hukum Islam", Jurnal Mazahib, Vol. 14. N0. 2. Huda, Chairul. (2008). Dari Tiada Pidana Tanpa Kesalahan. Prenada Media Group, Jakarta. Kementerian Agama RI, al-Qur’an dan Terjemahnya. Mukhlishin & Sarip. (2020). Keadilan dan Kepastian Hukum: Menyoal Konsep Keadilan Hukum Hans Kelsen Perspektif “Al-Adl” Dalam Al-Qur’an,Media Keadilan: Jurnal Ilmu Hukum, Vol. 11 No. 1. Moerdani. (2010). Hukum Islam. Jakarta: Pustaka Pelajar. Mushafi & Ismail Marzuki. (2018). Persinggungan Hukum dengan Masyarakat dalam Kajian Sosiologi Hukum, Jurnal Cakrawala Hukum, Vol. 9, No. 1. Rafida, Sinulingga & R Sugiharto. (2020).  Studi Komparasi Sanksi Pidana Pembunuhan dalam Kitab Undang-Undang Hukum Pidana (KUHP) dengan Hukum Islam dalam Rangka Pembaharuan Hukum Pidana, Sultan Agung Fundamental Research Journal, Vol. 1 No. 1. Raharjo, Sajipto. (2003). Sisi-sisi Lain dari Hukum di Indonesia, Cetakan I, Kompas, Jakarta. Roeslan, Saleh. (1987). Stelesel Pidana Indonesia. Jakarta: Aksara aru. Suheri, Ana. (2008). Wujud Keadilan dalam Masyarakat ditinjau dari Perspektif Hukum Nasional, Jurnal Morality, Vol. 4, No. 1, Juni. Wahyuningsih. (2013). Prinsip-Prinsip Individualisasi Pidana Dalam Hukum Pidana Islam dan Pembaharuan Hukum Pidana Indonesia. Semarang: Badan Penerbit Universitas Diponegoro.